2021
DOI: 10.3390/ijms22157832
|View full text |Cite
|
Sign up to set email alerts
|

Differential Domain Distribution of gnomAD- and Disease-Linked Connexin Missense Variants

Abstract: Twenty-one human genes encode connexins, a family of homologous proteins making gap junction (GJ) channels, which mediate direct intercellular communication to synchronize tissue/organ activities. Genetic variants in more than half of the connexin genes are associated with dozens of different Mendelian inherited diseases. With rapid advances in DNA sequencing technology, more variants are being identified not only in families and individuals with diseases but also in people in the general population without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…While calculating variant distributions along protein sequences can help to identify essential domains, it fails to consider the arrangement of variants in 3D space. 6 This has been addressed by manual mapping of variants 11 or computational mapping of variant depletion scores directly onto protein structures. For example, Hicks et al, developed a ‘3D Tolerance Score’ which compares an observed and expected number of missense variants in 5 Å-radius spheres around individual atoms in a 3D structure.…”
Section: Introductionmentioning
confidence: 99%
“…While calculating variant distributions along protein sequences can help to identify essential domains, it fails to consider the arrangement of variants in 3D space. 6 This has been addressed by manual mapping of variants 11 or computational mapping of variant depletion scores directly onto protein structures. For example, Hicks et al, developed a ‘3D Tolerance Score’ which compares an observed and expected number of missense variants in 5 Å-radius spheres around individual atoms in a 3D structure.…”
Section: Introductionmentioning
confidence: 99%
“…Second, hydrophobic residues are highly conserved in Cx46 and Cx50 as well as among α and other families of connexins, and the equivalent hydrophobic residue positions are almost all able to form amphipathic α-helix to likely interact with their TM1/2 domains. These hydrophobic residue positions are also frequently found to be hot spots for inherited disease-linked connexin mutants, such as oculodentodigital dysplasia-linked mutants in another α-connexin Cx43 (L7, L11) [ 44 ] and CMT1X-linked mutants in a β-connexin Cx32 on equivalent positions (W3, L9, L10) [ 37 ]. Functional studies on mutations of the hydrophobic NT residues of Cx32, including W3D, L6D, L9D, and L10D all resulted in non-functional GJs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was hampered by a lack of strong functional evidence evaluating the role of various domains in gap junction or hemichannel function. Ultimately, it was applied using data regarding the location of known disease-causing variants collated and assessed by Bai et al [143], which may result in circular arguments regarding the classification of variants in these regions that were used to define these regions. This is a limitation of the current approach and should be addressed for more accurate classifications in the future.…”
Section: Reclassification Of Literature Reported Gja3 and Gja8 Variantsmentioning
confidence: 99%